2013
DOI: 10.1680/macr.12.00040
|View full text |Cite
|
Sign up to set email alerts
|

Chloride diffusion coefficient and service life prediction of concrete subjected to repeated loadings

Abstract: The chloride diffusion coefficient and the service life of concrete with different water to cement (W/C) ratios and under repeated loadings were examined. The W/C ratios were 0·30, 0·35, 0·40 and 0·45 by mass of cement. Loading, repeated five times, was applied to concrete specimens using a WHY series fully automatic testing machine; the maximum loading was 40% and 80% of the axial cylinder compressive strength ( [Formula: see text]). The diffusion coefficients were calculated from the steady state in a chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In fact, recent researches [13] that deal with life cycle cost analyses of concrete bridges in corrosive environments and are based on preventive maintenance actions, use the 75-year period as service life. Such studies identify the 75-year period by averaging the service life reported from most DOTs in bridge projects that adopt CS as reinforcement [13].…”
Section: Service Life and Design Life Conceptmentioning
confidence: 99%
“…In fact, recent researches [13] that deal with life cycle cost analyses of concrete bridges in corrosive environments and are based on preventive maintenance actions, use the 75-year period as service life. Such studies identify the 75-year period by averaging the service life reported from most DOTs in bridge projects that adopt CS as reinforcement [13].…”
Section: Service Life and Design Life Conceptmentioning
confidence: 99%
“…-CP V RS [26], -w/c = 0.55 and 0.65 [11] -w/c = 0.32 [12] -OPC, HES, SCB*AL cement [3] -OPC, CEM I and CEM III/A [27] -w/c = 0,4 [28] -w/c = 0.4 -0.5 [29] -w/c = 0.30, 0.35, 0.40 and 0.45 [30] -PC equivalent to ASTM Type II [7] -w/c = 0.5 [31] [27] [7] -CEM I 42.5 N [24] -w/c = 0.55, 0.50, and 0.45 [25] -CEM IV/A-P 42.5R, CEM II/A-L 42.5R, and CEM III/A 42.5R [25] Water/Binder (W/B) ratio: Aggregate/cement ratios: 4 -6 [26] -W/B = 0.5 [3] -W/B = 0.4, 0.5, and 0.6 [5] Fly ashbinder ratios: 0.2, 0.35, and 0.5 [3] -W/B = 35%, 45%, 55% [15], -W/B = 0.47 [18] The volume fractions of coarse aggregate: -W/B = 0.4 and, 0,33 [24] -v = 0, 0.2, 0.3, 0.4, and 0.5. [15]…”
Section: Various Materials Used In Concrete Specimensmentioning
confidence: 99%
“…-wet-dry cycles [1] [32] -the stress influence coefficient [38]; -water saturation degrees: 50%, 75%, 90% and 100%. [26] -service life prediction [30] [31]…”
Section: Independent Variables Dependent Variablesmentioning
confidence: 99%
“…Most in-lab tests of chloride penetration into cement-based porous materials (CBPMs) were performed under free external stresses (Wongkeo et al 2013;Mercado-Mendoza et al 2013;Justnes et al 2016;Petcherdchoo 2016;Silva et al 2017;Vilasboas and Machado 2017). However, structures always service under external stresses, which implies that the in-lab free-loading transport mechanisms may be inadequate to represent the real transport processes, and consequentially may bias durability prediction (Zhang et al 2013). Therefore, it is of significant importance to understand how and to what extent external loads affect the chloride diffusivity in CBPMs.…”
Section: Introductionmentioning
confidence: 99%
“…By systematic experimental investigations, Wang and his collaborators measured the chloride distribution profiles of concretes under different compressive/tensile stresses, and assessed the changes of chloride diffusion coefficient by different loading levels (Wang et al 2011(Wang et al , 2016a(Wang et al , 2016b(Wang et al , 2016c. Zhang et al (2013) examined the chloride diffusion coefficient of concrete with different water-to-cement (w/c) ratios under repeated loadings, and found that both the environmental conditions and material proportions can obviously influence service life prediction. measured the chloride diffusion coefficients of concretes blended with fly ash and blast furnace slag under compressive/tensile loads, and indicated the important effect of cracks in high stress levels.…”
Section: Introductionmentioning
confidence: 99%